Theoretical study of influence of modification of the metal surface on magnitude of the field emission current in gradient-stable accelerating structures - Musiienko, I.I.; Kholodov, R.I. (Вопросы атомной науки и техники, 2019)
Quantum-mechanical problem on electron motion through the model potential barrier of the metal-vacuum system with an additional near-surface dipole layer is considered. Taking into account the continuity conditions of the wave functions and their derivatives at the interface between the two media, general expressions of the coefficient of transparency of the potential barrier and a current density of field emission is obtained in the framework of this model. It is shown the influence of the eﬀective thickness of the dipole layer of the metal surface on a value of the field emission current density. Розв’язана квантово-механічна задача про рух електрона через модельний потенціальний бар’єр системи метал-вакуум з введенням додаткового приповерхневого дипольного шару. Враховуючи умови неперервності хвильових функцій і їх похідних на межі розділу двох середовищ, одержано загальні вирази коефіцієнта прозорості потенціального бар’єра та густини струму польової емісії в рамках даної моделі. Показано вплив ефективної товщини дипольного шару поверхні металу на значення густини струму польової емісії. Решена квантово-механическая задача о движении электрона через модельный потенциальный барьер системы металл-вакуум с введением дополнительного приповерхностного дипольного слоя. Учитывая условия непрерывности волновых функций и их производных на границе раздела двух сред, получены общие выражения коэффициента прозрачности потенциального барьера и плотности тока полевой эмиссии в пределах данной модели. Показано влияние эффективной толщины дипольного слоя поверхности металла на значение плотности тока полевой эмиссии.